Business Process Reengineering Of Aviation Waste Management Based On Iso 14001: 2015 At Soekarno-Hatta Airport - Rezekia, Reza (Cv. Syntax Corporation Indonesia, 2021)
Introduction: The average daily flight waste at Soekarno-Hatta Airport is ±315 tons and will have an impact on passengers and the environment. This is due to the low recycling rate of waste management at Soekarno-Hatta Airport. Objective: This study aims to determine Business Process Reengineering (BPR) based on ISO 14001:2015, cost efficiency, and waste management performance at Soekarno-Hatta Airport. The method used in this research is an explanatory survey using descriptive and verification analysis. Results: The analytical approach uses Partial Least Square (PLS). Test the validity and reliability as well as data processing using WarpPLS 7.0 software. As a result, the performance of BPR, ISO 14001:2015, cost efficiency, and waste management at Soekarno-Hatta Airport has not been optimal. BPR has a positive and significant influence partially on cost efficiency and waste management performance. ISO 14001:2015 also has a significant and positive effect on cost efficiency and waste management performance. Cost efficiency has a positive and significant effect on the performance of waste management. However, it does not mediate the relationship between BPR variables and waste management performance and ISO 14001:2015 with waste management performance. Conclusion: BPR for aviation waste management at Soekarno-Hatta Airport was appropriate. This is proved by the management of PT AP-II already having an eco-airport master plan. However, it has not been socialized to the smallest unit, nor has HR training been carried out to carry out waste management. Soekarno-Hatta Airport already has ISO 14001: 2015 certificate, so the clauses in the form of variable dimensions ISO 14001: 2015 are by the manual or guidelines. Cost-efficiency for aviation waste management at Soekarno-Hatta Airport is not optimal considering that there is still a significant gap between waste management costs at Soekarno-Hatta Airport and waste management in other places. Soekarno-Hatta Airport's waste management performance is also not optimal with indicators of low recycling rates and high waste generation.